Pengaruh Kombinasi Kegel Exercise Cepat dan Kompres Hangat Terhadap Penurunan Nyeri Dismenore Pada Remaja Usia 12-14 Tahun - Arisandi, Desi Dwi, Totok BudiSantoso, S.Fis, S.Pd, M.Ph, Arif Pristianto, SSt.FT.,M.Fis (2016)
BACKGROUND: Dysmenorrhea is painful cramp at suprapubic area that can spread to the lumbosacralis area and legs. Primary dysmenorrhea is menstrual pain that's not a symptom of an underlying gynecologic disorder but is related to the normal process of menstruation. Some of non pharmalogical management on primary dysmenorrhea are fast kegel exercise and hot compress. Fast kegel exercise is known can stimulate the release of endorphins and then will increase pain threshold and hot compress is benefit for extensibility of soft tissue. OBJECTION: To determine the impact of fast kegel exercise and hot compress on decreasing pain of primary dysmenorrhea in adolescence 12-14 years old at Islamic Junior High School Rasau Jaya. RESEARCH METHODE: This research is quasy experimental model non randomized with pretes-posttest control group design method. This research held on 27th March until 21th May. The total sample is 24 respondents that divided into two groups, 12 respondents in intervention group adan 12 respondents in control group. Then the intervention group was given fast kegel exercise and hot compress, and control was given only hot compress. The respondents practiced everyday till a period of 8 weeks. RESULTS: Non parametric statistical, the results of bivariate data analysis using Wilcoxon test, the value of intervention group is p: 0,002 (p <0,05) while the value of control group is p: 0,105 (p <0,05 it means that combination of fast kegel exercise and hot compress are effective for decreasing pain of primary dysmenorrhea, and Mann Whitney test used to compare differences between intervention and control group, the value is p: 0,000 (p <0,05) it showed the difference of painful decreasing scale on intervention and control group. CONCLUSION: Combination of fast kegel exercise and hot compress are effective to decrease pain of primary dysmenorrhea. KATA KUNCI : primary dysmenorrhea, fast kegel exercise, hot compress